Studi Produksi Hidrasin VIA Proses Urea - J. P. Sitompul (Reaktor, 2005)
The use of hydrazine,N2H4 becomes very broad nowadays, in the production of polymer such as automobile air bags, in pharmacy, and in the water treatment for oxygen scavenge. Three commercial processes are available for hydrazine production , i.e. via Rasching-Olin, Ketazin, and Urea process. The operating condition for the later process is very mild compared to with the other two processes and hence requires simple processing equipments. This paper concerns with the kinetic study on production and on the effect of deactivator/ inhibitor during hydrazine bench-scale production via  Urea process. Operating condition are at 1 bar and at temperature range 5-100 0C. The yield of the hydrazine and its concentration with varying reactants, NaOH, hypochlorite, and urea during the cource of reaction are presented. Futher, the effect of gelatin as the deactivator toward hydrazine yield is futher examined. A kinetic model is proposed and used to predict yield of hydrazine. The predicted yield is in close agreement with the experimental yield.Keywords : hydrazine, bench-scale production, kinetic model, oxygen scavenger, inhibitor, geltine